The Activity of Carbohydrate-Degrading Enzymes in the Development of Brood and Newly Emerged workers and Drones of the Carniolan Honeybee, Apis mellifera carnica - Żółtowska, Krystyna (University of Wisconsin Library, 2012)

(untitled)
The activity of glycogen Phosphorylase and carbohydrate hydrolyzing enzymes α-amylase, glucoamylase, trehalase, and sucrase was studied in the development of the Carniolan honey bee, Apis mellifera carnica Pollman (Hymenoptera: Apidae), from newly hatched larva to freshly emerged imago of worker and drone. Phosphorolytic degradation of glycogen was significantly stronger than hydrolytic degradation in all developmental stages. Developmental profiles of hydrolase activity were similar in both sexes of brood; high activity was found in unsealed larvae, the lowest in prepupae followed by an increase in enzymatic activity. Especially intensive increases in activity occurred in the last stage of pupae and newly emerged imago. Besides α-amylase, the activities of other enzymes were higher in drone than in worker broods. Among drones, activity of glucoamylase was particularly high, ranging from around three times higher in the youngest larvae to 13 times higher in the oldest pupae. This confirms earlier suggestions about higher rates of metabolism in drone broods than in worker broods.